If my question is 16x - 6 = -4

What does x equal

11 answers

To solve the equation \( 16x - 6 = -4 \), follow these steps:

  1. Add 6 to both sides of the equation: \[ 16x - 6 + 6 = -4 + 6 \] This simplifies to: \[ 16x = 2 \]

  2. Divide both sides by 16 to isolate \( x \): \[ x = \frac{2}{16} \] This simplifies to: \[ x = \frac{1}{8} \]

So, \( x \) equals \( \frac{1}{8} \).

1/2 (6x - 10)

It looks like you want to simplify or evaluate the expression \(\frac{1}{2} (6x - 10)\).

Here’s how to simplify it:

  1. Distribute \(\frac{1}{2}\) to both terms inside the parentheses: \[ \frac{1}{2} (6x) - \frac{1}{2} (10) \]

  2. Calculate each term: \[ \frac{1}{2} (6x) = 3x \] \[ \frac{1}{2} (10) = 5 \]

Putting it all together, the expression simplifies to: \[ 3x - 5 \]

So, \(\frac{1}{2} (6x - 10) = 3x - 5\).

If my problem is 3x - 5 = 7x + 15
What does x equal?

To solve the equation \( 3x - 5 = 7x + 15 \), follow these steps:

  1. Get all terms involving \( x \) on one side and constant terms on the other side. Start by subtracting \( 3x \) from both sides: \[ -5 = 7x - 3x + 15 \] This simplifies to: \[ -5 = 4x + 15 \]

  2. Next, subtract 15 from both sides: \[ -5 - 15 = 4x \] This simplifies to: \[ -20 = 4x \]

  3. Divide both sides by 4 to isolate \( x \): \[ x = \frac{-20}{4} \] This simplifies to: \[ x = -5 \]

Thus, \( x \) equals \(-5\).

2 • (1/2m + 7)

To simplify the expression \( 2 \cdot \left(\frac{1}{2}m + 7\right) \), you can distribute the \( 2 \) to both terms inside the parentheses:

  1. Distribute \( 2 \): \[ 2 \cdot \left(\frac{1}{2}m\right) + 2 \cdot 7 \]

  2. Calculate each term: \[ 2 \cdot \left(\frac{1}{2}m\right) = m \] \[ 2 \cdot 7 = 14 \]

Putting it all together, the expression simplifies to: \[ m + 14 \]

So, \( 2 \cdot \left(\frac{1}{2}m + 7\right) = m + 14 \).

2 • ( m + 15)

To simplify the expression \( 2 \cdot (m + 15) \), you can distribute the \( 2 \) to both terms inside the parentheses:

  1. Distribute \( 2 \): \[ 2 \cdot m + 2 \cdot 15 \]

  2. Calculate each term: \[ 2 \cdot m = 2m \] \[ 2 \cdot 15 = 30 \]

Putting it all together, the expression simplifies to: \[ 2m + 30 \]

So, \( 2 \cdot (m + 15) = 2m + 30 \).

If my problem is m + 14 = 2m + 30
What does m equal?

To solve the equation \( m + 14 = 2m + 30 \), follow these steps:

  1. Get all terms involving \( m \) on one side and constant terms on the other side. Start by subtracting \( m \) from both sides: \[ 14 = 2m - m + 30 \] This simplifies to: \[ 14 = m + 30 \]

  2. Next, subtract 30 from both sides: \[ 14 - 30 = m \] This simplifies to: \[ -16 = m \]

Thus, \( m \) equals \(-16\).

Similar Questions
  1. QuestionSolve the equation for y: 3x+5y=60 (2 points) Responses y=−35x+12 y is equal to negative 3 fifths x plus 12 y=60+3x5 y
    1. answers icon 3 answers
  2. QuestionUsing the angle relationships, determine the value of y in the diagram above. (1 point) Responses y=15 y is equal to 15
    1. answers icon 1 answer
  3. Write y+3x=4in slope-intercept form. This question requires you to show your w) Responses y=3x+4 y is equal to 3 x plus 4
    1. answers icon 1 answer
  4. Simplify the rational expression. State any restrictions on the variable.(t^2 + t - 6)/(t^2 - 9) (t - 2)/(t-3), t not equal 3, t
    1. answers icon 1 answer
more similar questions